Measuring Intercultural Sensitivity of English Language Students at a Higher Education Institution in Indonesia - Sukardi Weda; Haryanto Atmowardoyo; Iskandar Abdul Samad; Siti Sarah Fitriani; Andi Elsa Fadhilah Sakti (TRANSBAHASA, 2022)
This study aims at measuring the intercultural sensitivity of English language students at a higher education institution in Makassar, Indonesia. The participants of the study were the first semester students of the English Literature Study Program from the Faculty of Languages and Literature, Universitas Negeri Makassar, who enrolled in the English Phonology course (N = 73, female = 61 (83.56%) and male = 12 (16.44%). The participants of the study were from the English Phonology course because the participants were from various ethnic group backgrounds. The instrument used for the study was Chen and Starosta’s Intercultural Sensitivity Scale (ISS) to explore the intercultural sensitivity of English language students. The findings reveal that the subjects enjoy interacting with people from different cultures. It was also found that: 1) The participants respected the values of people from different cultures, 2) They felt confident when interacting with people from different cultures, 3) They are pretty sure of themselves in interacting with people from different cultures, 4) They respect the values of people from different cultures, 5) They often give positive responses to their culturally different counterpart during their interaction.